Bioadhesive tablets containing cyclodextrin complex of itraconazole for the treatment of vaginal candidiasis - DURMUŞOĞLU, LÜTFİYE (ELSEVIER, 2014)
Itraconazole (ITR) is commonly used in the treatment of Candida infections. It has a nephrotoxic effect and low bioavailability in patients who suffer from renal insufficiency, and its poor solubility in water makes ITR largely unavailable. Cyclodextrins (CyDs) are used to form inclusion complexes with drugs to improve their aqueous solubility and to reduce their side effects. In this study, ITR was complexed with gamma-cyclodextrin (gamma-CyD), hydroxypropyl-beta-cyclodextrin (HP-beta-CyD), methyl-beta-cyclodextrin (Met-beta-CyD) and sulphobutyl ether-beta-cyclodextrin (SBE7-beta-CyD) to increase its water solubility and to reduce the side effects of the drug without decreasing antifungal activity. Complex formation between ITR and CyDs was evaluated using SEM,H-1 NMR and XRD studies. The antifungal activity of the complexes was analyzed on Candida albicans strains, and the susceptibility of the strains was found to be higher for the ITR-SBE7-beta-CyD complex than for the complexes that were prepared with other CyDs. Vaginal bioadhesive sustained release tablet formulations were developed using the ITR-SBE7-beta-CyD inclusion complex to increase the residence time of ITR in the vagina, thereby boosting the efficacy of the treatment. The swelling, matrix erosion and bioadhesion properties of formulations and the drug release rate of these tablets were analyzed, and the most therapeutically effective vaginal formulation was determined. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Itraconazole; Cyclodextrin; Vaginal candidiasis; Vaginal tablet; Mucoadhesion; HYDROXYPROPYL-BETA-CYCLODEXTRIN; IN-VITRO; INCLUSION COMPLEX; PHARMACEUTICAL APPLICATIONS; PHARMACOLOGICAL-PROPERTIES; RELEASE; BIOAVAILABILITY; DISSOLUTION; SOLUBILITY; PHARMACOKINETICS